Publishing for a Varied Public: An Empirical Study. - Windal, Floyd W. (The Accounting Review, 1981)
Abstract ABSTRACT: Previous studies analyzing the publication rates of various accounting faculties concentrated upon only four journals, two of which were primarily academic. This study examines publications in 12 journals, representing the much broader audience addressed by accounting authors. The 25 schools with the largest number of publications are listed both on a total publications basis and on the basis of average output per faculty member. The concentration of effort by some schools on particular segments of the audience is highlighted.